2018
DOI: 10.3390/jsan7010014
|View full text |Cite
|
Sign up to set email alerts
|

An Interface for IoT: Feeding Back Health-Related Data to Parkinson’s Disease Patients

Abstract: This paper presents a user-centered design (UCD) process of an interface for Parkinson's disease (PD) patients for helping them to better manage their symptoms. The interface is designed to visualize symptom and medication information, collected by an Internet of Things (IoT)-based system, which will consist of a smartphone, electronic dosing device, wrist sensor and a bed sensor. In our work, the focus is on measuring data related to some of the main health-related quality of life aspects such as motor functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
45
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 18 publications
0
45
0
1
Order By: Relevance
“…The process of developing a smart parking system by including the relevant users or stakeholder and the positive outcome of the project highlight that participatory-and user centred design methodologies are invaluable for the overall design process but in particular the early stages of project development. This postulation is supported through diverse academic literature [10,12]. Consistency, intuitive design and good, logical mapping are just some of the cornerstones for the successful uptake of any design as illustrated by Don Norman in his book "The Design of Everyday Things" [21].…”
Section: How Practical Is Agile In Conjunction With Ucd?mentioning
confidence: 98%
See 1 more Smart Citation
“…The process of developing a smart parking system by including the relevant users or stakeholder and the positive outcome of the project highlight that participatory-and user centred design methodologies are invaluable for the overall design process but in particular the early stages of project development. This postulation is supported through diverse academic literature [10,12]. Consistency, intuitive design and good, logical mapping are just some of the cornerstones for the successful uptake of any design as illustrated by Don Norman in his book "The Design of Everyday Things" [21].…”
Section: How Practical Is Agile In Conjunction With Ucd?mentioning
confidence: 98%
“…For example, in a system developed for Parkinson's disease, patients it was found that 70% of users reacted positively to a IoT-based system prototype, (connected devices such as a wrist sensor, smartphone, bed sensor and an electronic dosing device). Positive impact of the system is due to including user in application/system development [12]. It was found that challenge of communication has been one of major component for hindering implementation of UX in the IoT domain.…”
Section: Activity Centred Design (Acd) Vs User Centred Design (Ucd)mentioning
confidence: 99%
“…Six papers have been selected in this special issue that respond to questions raised [1][2][3][4][5][6]. The first paper, entitled "Design, Fabrication, and Testing of an Internet Connected Intravenous Drip Monitoring Device" submitted by researchers from German universities, presents a monitoring system retro-fittable for existing Intravenous (IV) infusion setup that leverages human based estimations of time required by an IV bottle to empty, which makes the IV therapy vulnerable to human error [1].…”
mentioning
confidence: 99%
“…Paper 3 is entitled "An Interface for IoT: Feeding Back Health-Related Data to Parkinson's disease Patients" and submitted by authors from Sweden. It presents a user-centered design (UCD) process of an interface for Parkinson's disease (PD) patients to help them better manage their symptoms [3]. The system aims to provide useful information to patients related to their symptom and medication.…”
mentioning
confidence: 99%
See 1 more Smart Citation